Dithienogermole-based solution-processed molecular solar cells with efficiency over 9%. Issue 55 (20th June 2016) - Gupta, Vinay; Lai, Lai Fan; Datt, Ram; Chand, Suresh; Heeger, Alan J.; Bazan, Guillermo C.; Singh, Surya Prakash
Abstract : A molecular donor of intermediate dimensions based on dithienogermole (DTG) as the central electron rich unit, coded as DTG(FBT2 Th2 )2, was designed and synthesized for use in bulk heterojunction, solution-processed organic solar cells. Abstract : A molecular donor of intermediate dimensions based on dithienogermole (DTG) as the central electron rich unit, coded as DTG(FBT2 Th2 )2, was designed and synthesized for use in bulk heterojunction, solution-processed organic solar cells. Under optimized conditions, a maximum power conversion efficiency (PCE) of 9.1% can be achieved with [6, 6]-phenyl C71 -butyric acid methyl ester (PC71 BM) as the acceptor semiconductor component.